Addressing Obesity to Promote Healthy Aging - Roderka, Meredith N; Puri, Sadhana; Batsis, John A (Clinics in geriatric medicine, 2020)
The population worldwide is aging and prevalence of obesity in this population is increasing. The range of consequences that effect these at-risk patients include increased risk of falls, fractures, reduced quality of life, and cognitive decline. This article describes the epidemiology of obesity, risks and benefits of weight loss, and importance of treating obesity to help promote healthy aging. Health care professionals should encourage older adults with obesity to implement healthy lifestyle behaviors including exercise and diet routine. Treating obesity in older adults mitigates the significant public health crisis, and reduces health care utilization and risk of long-term adverse events.